The Role of TLR2 in Infection and Immunity - de Oliviera Nascimento, Laura; Massari, Paola; Wetzler, Lee M. (Frontiers in Immunology, 2012)
Toll-like receptors (TLRs) are recognition molecules for multiple pathogens, including bacteria, viruses, fungi, and parasites. TLR2 forms heterodimers with TLR1 and TLR6, which is the initial step in a cascade of events leading to significant innate immune responses, development of adaptive immunity to pathogens and protection from immune sequelae related to infection with these pathogens. This review will discuss the current status of TLR2 mediated immune responses by recognition of pathogen-associated molecular patterns (PAMPS) on these organisms. We will emphasize both canonical and non-canonical responses to TLR2 ligands with emphasis on whether the inflammation induced by these responses contributes to the disease state or to protection from diseases.